Analisis Perencanaan Program Penyuluhan Dampak Makanan Cepat Saji Terhadap Kesehatan Remaja Melalui Media Digital - Irfan Sazali Nasution; Wiwin Ariani; Izmi Raditya Putri; Nurul Hidayah; Natasya Balqis; Tazla Nia Fareby; Afrida Dina Pratiwi (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
The use of digital media in health education is crucial to raising teenagers' awareness about the dangers of fast food consumption. The high trend of consuming convenient foods poses risks such as obesity and metabolic diseases, necessitating innovative and effective educational strategies. This study employs a descriptive quantitative approach with survey methods, involving 50 active social media-using teenagers interacting with online content. The results indicate that digital media in the form of short videos and interactive visual content can significantly improve teenagers' knowledge and perceptions of the hazards associated with fast food, although their consumption habits remain high. These findings confirm the importance of leveraging digital media in health promotion as a strategic step in preventing long-term health risks among teenagers.